(untitled) - Judd, Ashley; Gamble, Nathan; Kristofferson, Kris; Freeman, Morgan; Smith, Charles Martin; Warner Home Video (Firm) (Alcon Entertainment / Warner Home Video, 2014)
Winters surrogate mother, the very elderly dolphin Panama, has passed away, leaving Winter without the only poolmate she has ever known. However, the loss of Panama may have even greater repercussions for Winter, who, according to USDA regulations, cannot be housed alone, as dolphins social behavior requires them to be paired with other dolphins. Time is running out to find a companion for her before the team at Clearwater loses their beloved Winter to another aquarium.
Keywords: Behavior; Dolphins; Aquariums; Drama; Aquariums; Drama; Behavior; Dolphins; Fiction films; Video recordings for the hearing impaired; Animal films; Feature films; Video recordings for the hearing impaired; Animal films; Drama; Feature films; Fiction films